Manajemen Nyeri Distraksi Berbasis Virtual Reality (VR) - Ervin Septian Dewi; Masfuri Masfuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of Virtual Reality (VR) as a distraction technique in pain management. The method used in this research is a literature study through online databases: EBSCOhost, PubMed, and Scopus, with free full-text criteria, using English, publications in the last five years, and clinical trial or randomized controlled trial research designs. The results showed that there were 1,012 articles, with six pieces according to the inclusion criteria, which identified the effectiveness of Virtual Reality (VR) in reducing pain, anxiety, vital signs, experiences, levels of satisfaction, and side effects. In conclusion, Virtual Reality (VR) can be a distraction method to reduce pain, anxiety, and patients' vital signs. VR produces a positive and fun experience that is also considered feasible and safe. Keywords: Distraction, Comfort, Pain, Virtual Reality